1971
DOI: 10.1111/j.1469-7998.1971.tb02177.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of small rodents in Mayanja Forest, Uganda

Abstract: With 24 figures in the text) 1148 small rodents representing 16 species were caught in Mayanja Forest, Uganda from regular trappings between September, 1967 and August, 1968 inclusive. These were restricted to five compartments which had been subjected to extensive felling in 1962-65 leaving at the time of the survey a dense herbage and scrub. Rain fell in all months of the year with the wettest periods from September to November and February to May.The most frequently caught species on the ground (Praomys mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…Delany (1964) found little evidence of breeding amongst grassland rodents in Uganda during the period following the major rains and Neal (1968) confirmed that peak reproductive activity in most species occurred during the two rainy seasons. Reproduction in certain forest and desert rodents has also been found to occur principally during the rainy season (Delany, 1971, Happold, 1966. In contrast, Mastomys on the Kafue River flats in Zambia has been observed to commence breeding towards the end of the dry season (Sheppe, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Delany (1964) found little evidence of breeding amongst grassland rodents in Uganda during the period following the major rains and Neal (1968) confirmed that peak reproductive activity in most species occurred during the two rainy seasons. Reproduction in certain forest and desert rodents has also been found to occur principally during the rainy season (Delany, 1971, Happold, 1966. In contrast, Mastomys on the Kafue River flats in Zambia has been observed to commence breeding towards the end of the dry season (Sheppe, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Group 2 Praomys tullbergi, P. stella and Stochomys defua-are mainly vegetarian and forage at night. They are partly arboreal (Booth, 1960;Delany, 1971;Eisentraut, 1963;Hayman, 1935;Heim de Balsac & Aellen, 1965). Praomys tullbergi and Stochomys defua are larger than P. stella.…”
Section: Discussionmentioning
confidence: 99%
“…Cheeseman and Delany (1979) went a step further in determining densities and energetics in grassland populations. In his forest study, Delany (1971) examined vertical distribution, favoured vegetation, behaviour, activity and diet in defining the niche of each species.…”
Section: The Post-second World War Expansionmentioning
confidence: 99%
“…Detailed studies then followed on breeding cycles and life histories in savanna by Neal (1977aNeal ( , 1977b and in forests by Delany (1971), Okia (1973) and Isabirye-Basuta 7 . Cheeseman and Delany (1979) went a step further in determining densities and energetics in grassland populations.…”
Section: The Post-second World War Expansionmentioning
confidence: 99%